Pengembangan Sumber Daya Manusia untuk Mendorong Pertumbuhan Industri Kreatif di Desa Cicalengka Tangerang - Hafis Laksmana Nuraldy; Surya Budiman; Yeti Kusmawati (Jurnal PKM Manajemen Bisnis, 2026)
The rapid growth of the creative industry in Indonesia requires the development of human resources capable of producing innovative and economically valuable products. This community service activity (PKM) was conducted to strengthen the skills and knowledge of the local community in managing waste into creative products. The main objective of this PKM was to empower the members of the Cicalengka Village waste bank to enhance their creativity, entrepreneurial mindset, and economic independence through sustainable waste management practices. The activity took place on November 2, 2025, involving 8 lecturers from Universitas Pamulang as facilitators and 49 community participants. The implementation method included material presentation, hands-on practice, group discussion, and question-and-answer sessions. The program was carried out in three stages: preparation, implementation, and reporting. The results of the activity showed an increase in participants’ understanding of creative product design, marketing strategies, and the economic potential of recycled materials. Participants also demonstrated improved skills in processing waste into marketable products, indicating a positive impact on local creative industry development.